Tree-ring based May-June streamflow reconstruction of Zemu River in the Eastern Himalaya - Nazimul Islam; Torsten Vennemann; Ulf Büntgen; Paul J. Krusic; Santosh K. Shah; Stuart N. Lane (Journal of Hydrology: Regional Studies, 2025)
Study region: Zemu River, Upper Teesta River Basin, Eastern Himalaya Study focus: In this study, a tree-ring chronology of Abies densa was used as a proxy to reconstruct a century-long May-June streamflow of the Zemu River. The reconstruction was carried out based on a scaling approach which explained 35 % of variance in observed streamflow and was varified by comparing with other regional reconstructions. Moving windowed Pearson correlation was performed to reveal the temporal influence of major climate forcings (e.g., ENSO) with the streamflow of Zemu River. New hydrological insights for the region: Our study identified a strong negative relationship between tree-growth and observed May-June streamflow in the glacier-fed Zemu River. This counterintuitive, inverse relationship is likely due to the contribution of additional meltwater when conditions are dry and insulation over the glacier is high. The reconstructed streamflow record reveals several high- and low-flow periods above and below the mean value (+/- 1σ) and identifies 30 high-flow years and 33 low-flow years, including some historically recorded floods in 1927, 1968, 1980, 1982 and 1998, and of severe droughts in 1951, 1976 and 2017. Most recently, a positive association between reconstructed streamflow and the ENSO has become apparent, which we attribute to reduced penetration of the Indian Summer Monsoon during ENSO years, which reduces precipitation but maintains for longer warmer and drier conditions that allow glacier melt.